A multiscale DEM-VOF method for the simulation of three-phase flows. (February 2018) - Pozzetti, Gabriele; Peters, Bernhard
Highlights: A multiscale DEM-VOF coupling is proposed to simulate three-phase flows. It produces grid-convergent solutions for the fluid phase. It can reproduce droplet formation and interface perturbations from a single particle. It is validated against three-phase flows presented in the literature. Abstract: A novel multiscale approach for three-phase flows is presented. The goal of the proposed method is to solve arbitrary three-phase flow configurations in a computationally efficient way, and in particular taking into account the effects of different length scales while sharply reducing the computational burden. This is particularly important in chemical, environmental, and process engineering, where large-scale quantities are normally of interest, but small-scale dynamics cannot be neglected. The method is based on the definition of two different length scales: the bulk scale, and the fluid fine scale. A dual-grid approach is adopted in order to resolve the bulk scale with information from the fluid fine scale. It is shown that the described method succeeds in delivering more accuracy than a standard approach based on the volume averaging technique, still, it remains suitable for the solution of real interest problems. The method is shown to successfully satisfy experimental results presented in the literature. Examples of three-phase flows simulations are provided to show how the proposed numerical approach can describe the physics of particle-laden, free surface flows with competitive computational cost. It is shown how the proposed method can naturally extend the DEM-VOF method to the presence of complex interface dynamics.